Rare case of gastric perforation with malrotation and volvulus: A case report - Pathak, Manish; Biangchwadaka, Suchiang; Narula, Dipanshu (International Journal of Medical Research and Review, 2016)
Gastric perforation in neonate has always been a catastrophe associated with high morbidity. The high mortality rate reflects to a certain extent the precariousness of the neonatal period, but the process evolves so rapidly that prompt diagnosis is necessary if improved survival rates are to be achieved. It is a mysterious entity regarding its cause, but three mechanisms; spontaneous perforation, trauma and ischemia are acceptable reasons for neonatal gastric perforation. Nonetheless, we present you here a rare case of malrotation with mid gut volvulus which presented with apparently spontaneous gastric perforation (1x1cm). Primary repair of the perforation with derotation of the volvulus was done. We question the spontaneity of neonatal gastric perforation and urge the need to look for the contributing cause.